Integrated Curriculum Development for Transdisciplinary Islamic Religious Education Subjects in the Society 5.0 Era - Maula, Atika Rofiqatul (Proceeding International Conference on Religion, Science and Education, 2022)
A digital transformation has surprised many parties, where the use of the internet in various sectors has encouraged people’s activities and become a new policy in the industry. One of the sectors that must be adapted to this transformation is education. So, this article discusses the integrated curriculum, especially Islamic religious education subjects (PAI) in the Society 5.0 era. The method of this article is a literature research that the data sources are obtained from relevant journal articles, books, and news. The integrated curriculum is a learning approach that is quite relevant to the rapid development of technology. Improvement in curriculum design is a constructive attitude so that students get comprehensive, meaningful, active, authentic, and simple learning. The development of an integrated curriculum is relevant with the current conditions of scientific transdisciplinary, such as in Islamic Religious Education subjects. From that concept, the students can solve various life problems with new discoveries obtained from a combination of scientific fields. Integrated curriculum development can be actualized in learning materials, strategies and learning methods.